The Sausage of the Future, Carolien Niebling (2017). (1st October 2019) - Hu, Ray
The Sausage of the Future, Carolien Niebling (2017)Zürich: Lars Müller Publishers, 156 pp., ISBN 978-3-03778-548-5, p/bk, €28